2017
DOI: 10.14715/10.14715/cmb/2017.63.12.12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of protein levels of autophagy markers (Beclin 1 and SQSTM1/p62) and phosphorylation of cyclin E in the placenta of women with preeclampsia

Abstract: Preeclampsia is a severe multisystem disorder, and its pathophysiology is still not completely understood. Autophagy, a recycling process that maintains cellular homoeostasis during differentiation and development, is controversial regarding increased or decreased autophagic activity in preeclampsia. The aim of this study was to determine whether autophagy is increased in the placentas of women with preeclampsia by examining the protein levels of autophagy markers (Beclin 1 and SQSTM1/p62) and phosphorylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Recently, some scholars have found that trophoblast autophagy plays a role in the pathogenesis of severe pre‐eclampsia. Numerous studies have shown that pre‐eclampsia patients have severe placental ischaemia and that this environment can promote autophagy . When excessive autophagy occurs in placental chorionic trophoblasts, it causes the death of trophoblasts .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some scholars have found that trophoblast autophagy plays a role in the pathogenesis of severe pre‐eclampsia. Numerous studies have shown that pre‐eclampsia patients have severe placental ischaemia and that this environment can promote autophagy . When excessive autophagy occurs in placental chorionic trophoblasts, it causes the death of trophoblasts .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that pre-eclampsia patients have severe placental ischaemia and that this environment can promote autophagy. 8,9 When excessive autophagy occurs in placental chorionic trophoblasts, it causes the death of trophoblasts. 10,11 Additionally, a report showed that damaged autophagy in extravillous trophoblast cells contributed to developing pre-eclampsia pathophysiology.…”
mentioning
confidence: 99%
“…They jointly regulate the generation of autophagosomes, and P62 is involved in autophagy degradation. The LC3-II to LC3-I ratio is currently recognized as an important marker of autophagy activation [ 26 , 27 ]. Because these factors are closely related to the activation and activity of autophagy, their expression levels in DCI patients are often used to infer autophagy activity.…”
Section: Resultsmentioning
confidence: 99%
“…Each step of autophagic flux is tightly regulated by a myriad of evolutionally conserved proteins encoded by the autophagy-related genes ( Figure 1 A). However, which regulatory molecules in the autophagy–lysosomal pathway are dysregulated in the placenta or the cellular models of PE remain poorly understood [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%